IDENTIFIKASI PENGEMBANGAN KECAKAPAN SOSIAL DALAM KELOMPOK PADUAN SUARA THE COUNTER MELODY (DCM) - Neonufa, Jeri Kristovel; Pareira, Mariana Ikun RD; Klau, Erni Raster (Universitas Nusa Cendana, 2023)
This research is included in qualitative research with a descriptive approach. The subjects of this study were one trainer and four members of The Counter Melody (DCM) choir which became the source of research data, which was carried out through interview techniques, and documentation studies. This data collection is carried out with stages, namely assessing data quality, data analysis, interpreting data and making conclusions on its findings. From the results of research conducted by researchers related to social skills, there is a positive change from each member of The Counter Melody choir in obeying the rules, accepting the consequences of every decision taken so that each participant can build good communication in achieving harmony and cooperation in the choir group.The conclusion of this study is that through the development of social skills, a person can establish communication relationships and establish good cooperation, and from the results of this study it can be seen that there are positive changes from each choir member so as to create harmony and cooperation in the counter melody choir group. Keywords : Development, Social Skills, Choir (DCM)